Clinically relevant doses of vitamin A decrease cortical bone mass in mice. Issue 3 (December 2018) - Lionikaite, Vikte; Gustafsson, Karin L; Westerlund, Anna; Windahl, Sara H; Koskela, Antti; Tuukkanen, Juha; Johansson, Helena; Ohlsson, Claes; Conaway, H Herschel; Henning, Petra; Lerner, Ulf H
Abstract : Excess vitamin A has been associated with decreased cortical bone thickness and increased fracture risk. While most studies in rodents have employed high dosages of vitamin A for short periods of time, we investigated the bone phenotype in mice after longer exposure to more clinically relevant doses. For 1, 4 and 10 weeks, mice were fed a control diet (4.5 µg retinyl acetate/g chow), a diet modeled from the human upper tolerable limit (UTL; 20 µg retinyl acetate/g chow) and a diet three times UTL (supplemented; 60 µg retinyl acetate/g chow). Time-dependent decreases in periosteal circumference and bone mineral content were noted with the supplemented dose. These reductions in cortical bone resulted in a significant time-dependent decrease of predicted strength and a non-significant trend toward reduced bone strength as analyzed by three-point bending. Trabecular bone in tibiae and vertebrae remained unaffected when vitamin A was increased in the diet. Dynamic histomorphometry demonstrated that bone formation was substantially decreased after 1 week of treatment at the periosteal site with the supplemental dose. Increasing amount of vitamin A decreased endocortical circumference, resulting in decreased marrow area, a response associated with enhanced endocortical bone formation. In the presence of bisphosphonate, vitamin A had no effect on cortical bone, suggesting that osteoclasts are important, even if effects on bone resorption were not detected by osteoclast counting, genes in cortical bone or analysis of serum TRAP5b and CTX. In conclusion, our results indicate that even clinically relevant doses of vitamin A have a negative impact on the amount of cortical bone.